Laboratory study on the suitability of nano-silica as a modifier for asphalt binders - Sukhija M.; Saboo N.; Yadav A.K.; Rath C. (My University, 2025)
This paper reports the laboratory investigations carried out to assess the effect of nanosilica (NS) on the physical, morphological and rheological properties of asphalt binder. Two base binders (VG 10 and VG 30) are modified using two dosages of laboratory prepared NS (2% and 4%) by weight of the base asphalt binder. Rheological studies (10–70°C) include high temperature performance grading (PG), frequency sweep, multiple stress creep and recovery (MSCR) and linear amplitude sweep (LAS) tests. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) studies are also done to understand the structural modification process. It is found that NS induces amorphous nature to the base asphalt binder, as observed from XRD. SEM images show inclusions of NS as a layered interlocking network within the base asphalt binder. The true failure temperature, in high temperature PG grading, increased with the increase in percentage of NS. |G*|/sinδ master curve indicates improvement in rutting characteristics with increase in dosage of NS. The extent of improvement is found to be binder dependent. Since the stiffness of the base asphalt binder increases, |G*|·sinδ master curve drawn at 20°C shows loss in fatigue resistance by inclusions of NS. In MSCR test, the rutting resistance of NS modified asphalt binder is found to be higher than the base binder. The addition of 4% NS in VG10 increases the rutting resistance by approximately 6 times, whereas it is approximately 2 times for VG30. In VG10 the stress sensitivity reduces by 48% and 74%, respectively, by addition of 2% and 4% NS. The results from LAS test are not conclusive. Statistical analysis indicates that NS has no significant effect on the fatigue life of base asphalt binders, irrespective of test temperature. In general, it is concluded that NS modification is more beneficial for locations with high pavement temperatures and heavy vehicular loading conditions. © 2021 Elsevier Ltd